2021
DOI: 10.1136/jitc-2020-002248
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant immunotherapy for non-small cell lung cancer: right drugs, right patient, right time?

Abstract: Standard curative treatment of early-stage non-small cell lung cancer (NSCLC) involves surgery in combination with postoperative (adjuvant) platinum-based chemotherapy where indicated. Preoperative (neoadjuvant) therapies offer certain theoretical benefits compared with adjuvant approaches, including the ability to assess on-treatment response, reduce the tumor bulk prior to surgery, and enhance tolerability in the preoperative setting. Indeed, the use of neoadjuvant therapies are well established in other can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 76 publications
1
37
0
2
Order By: Relevance
“…Pre-operative and/or post-operative treatments of NSCLC by targeted therapies or by immunotherapy (in association or not with chemotherapy) have recently revolutionized the care of early stage lung cancers and thus may prevent recurrence and progression of these tumors after surgery. Apart from the targeted therapy which has been described above, early stage NSCLC wild type for EGFR and ALK can benefit from neoadjuvant and/or adjuvant immunotherapy or immunochemotherapy in the context of ongoing large phase 3 clinical trials [3,6,12,13,17]. Therefore, these treatments provide great hope for a cure for all these cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-operative and/or post-operative treatments of NSCLC by targeted therapies or by immunotherapy (in association or not with chemotherapy) have recently revolutionized the care of early stage lung cancers and thus may prevent recurrence and progression of these tumors after surgery. Apart from the targeted therapy which has been described above, early stage NSCLC wild type for EGFR and ALK can benefit from neoadjuvant and/or adjuvant immunotherapy or immunochemotherapy in the context of ongoing large phase 3 clinical trials [3,6,12,13,17]. Therefore, these treatments provide great hope for a cure for all these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these associated treatments provided a moderate benefit in terms of progression-free survival and overall survival [3,4]. The recent results of adjuvant therapy targeting activating mutations in EGFR (exon 19 deletion and L858R mutation) and of preoperative immunotherapies of early stage (I-IIIA) NSCLC open up great perspectives for the prevention of relapse and/or post-operative tumor progression [6][7][8][9][10][11][12][13][14]. In this context, laboratories of pathology have been required to meet new challenges in developing a number of analyses to assure optimal care of patients in a routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 expression and bTMB levels were reported to correlate with response rate and PFS of anti-PD-L1 ICIs in the treatment of advanced NSCLC [ 128 , 129 ]. Pretreatment PD-L1 expression and TMB levels were also tested in neoadjuvant ICIs trials of early-stage NSCLC including NEOSTAR, LCMC3, NADIM and Forde et al trials [ 78 , 79 , 83 , 87 , 89 , 130 ]. The MPR was positively and significantly associated with the PD-L1 expression level in the NEOSTAR trial but was not significantly associated with the PD-L1 expression level in LCMC3, NADIM, and Forde et al studies [ 78 , 79 , 83 , 87 , 89 , 130 ].…”
Section: Future Perspectives: the Challenges Of Immunotherapy In Surgically Resectable Nsclcmentioning
confidence: 99%
“…Pretreatment PD-L1 expression and TMB levels were also tested in neoadjuvant ICIs trials of early-stage NSCLC including NEOSTAR, LCMC3, NADIM and Forde et al trials [ 78 , 79 , 83 , 87 , 89 , 130 ]. The MPR was positively and significantly associated with the PD-L1 expression level in the NEOSTAR trial but was not significantly associated with the PD-L1 expression level in LCMC3, NADIM, and Forde et al studies [ 78 , 79 , 83 , 87 , 89 , 130 ]. TMB was associated with MPR in the study of Forde et al but was not observed in the LCMC3 trial [ 78 , 79 , 89 ].…”
Section: Future Perspectives: the Challenges Of Immunotherapy In Surgically Resectable Nsclcmentioning
confidence: 99%
See 1 more Smart Citation